Cultural Tourist Market Reference for Destination Management Saung Angklung Mang Udjo Bandung, Jawa Barat - Nugraha, Rizki Nurul; Dewi, Liliana (West Science Social and Humanities Studies, 2025)
Indonesia has a lot of attractive tourism destinations, which are natural destinations, cultural destinations, and also man-made destinations. West Java, especially Bandung City which is usually called Paris Van Java, has so many attractive tourism destinations, one of the famous tourism destinations is cultural destinations. Every Tourist has a dream to visit Bandung, to enjoy the exoticism of Bandung. One of the famous cultural destinations is called "Saung Angklung Mang Udjo", which is this destination being a very attractive destination for international tourists. Angklung performance, traditional dance, and also puppet show, making things a destination as a central cultural destination in Bandung City. In Saung Angklung Udjo there is an angklung workshop area, tourists can learn how to make angklung, which is angklung is one of the Sundanese traditional music instruments. For known that cultural destination, every visitor places a number from 1 to 10 which means the number for position visitor. By getting to know visitors, managers can understand the characteristics of their visitors, so they can provide the services desired by their tourism market,